Stock photos of the Medford/Somerville campus, including the garden behind the Hillel Center and Tisch Library. Photo 006 - Schutzengel, Aaron (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including the garden behind the Hillel Center and Tisch Library.